A better way to implement the QOMS proforma for oncology and reconstruction. Issue 1 (January 2022) - Howells, Ryan; Nezamivand-Chegini, Soudeh; Schilling, Clare
Abstract : Introduction: The BAOMS Quality Outcomes in Oral and Maxillofacial Surgery (QOMS) registries were first rolled out between December 2019 – March 2020 in a pilot-audit, following recommendations for the speciality from the Get it Right First Time (GIRFT) initiative in 2018. At University College Hospital London (UCLH) the QOMS registries are an important part of our daily oncology and reconstruction workflow, and we have worked hard to streamline the significant data collection process. Methods: We adapted the original QOMS paper proformas and produced five bespoke electronic proforma documents, which were fully integrated with our EHRS system - Epic. We customised certain aspects of the documents to better suit the specific case-mix and work patterns of our unit, thereby reducing unnecessary clutter and irrelevant data points. Each proforma is delegated to a named member of the OMFS H&N MDT: Proforma 1 (pre-op) – H&N Clinical Nurse Specialist Proforma 2 (Surgery) – Speciality Registrar Proforma 3 (Discharge) – SHO or equivalent Proforma 4 (6 week F/U) – Speciality Registrar Proforma 5 – (2 year F/U) - Consultant Results: We began collecting data in April 2021, and since this time as a unit we have dealt with 32 Female and 43 Male surgical cases, between a team of 5 surgeons. We have near 100% completion of Proformas 1-4, which demonstrates the efficiency of this approach. Conclusions: We have shown how the potentially time-consuming and tedious process of data collection for QOMS can be streamlined and integrated into a daily workflow through the strategic use of custom proformas and designation of roles.